2003
DOI: 10.1103/physrevb.67.045312
|View full text |Cite
|
Sign up to set email alerts
|

Microtwinning in microcrystalline silicon and its effect on grain-size measurements

Abstract: Microcrystalline silicon grown by plasma-enhanced chemical vapor deposition consists of a phase mixture of amorphous silicon and submicrometer sized columnar crystalline silicon grains. These grains do not exhibit perfect translational symmetry but show a high density of microtwins, evidenced by structural investigations by use of transmission electron microscopy and x-ray diffraction. The high twin fault density of typically every tenth ͕111͖ bilayer leads to anisotropic size broadening effects for Bragg refl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
14
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 30 publications
3
14
1
Order By: Relevance
“…This thickness is supported by the phase diagrams measured using real-time spectroscopic ellipsometry by Collins et al 25 A Gaussian dangling-bond distribution model with a standard deviation of 0.2 eV was adopted to describe the broad distribution of dangling bonds. 26,27 The overall material parameters employed in the simulation is tabulated in the Appendix (see Table II). Fig.…”
Section: Samplesmentioning
confidence: 99%
“…This thickness is supported by the phase diagrams measured using real-time spectroscopic ellipsometry by Collins et al 25 A Gaussian dangling-bond distribution model with a standard deviation of 0.2 eV was adopted to describe the broad distribution of dangling bonds. 26,27 The overall material parameters employed in the simulation is tabulated in the Appendix (see Table II). Fig.…”
Section: Samplesmentioning
confidence: 99%
“…14 For samples with coherently diffracting regions (i.e., the regions between twins and/or regions containing no stacking faults or dislocations) larger than approximately 100 nm, these broadening contributions are much smaller than the contributions due to coherent domain size and strain and can be neglected. 14,31 For a polycrystalline thin film (Figure 2(a)), the measured intensity is the sum of the diffracted intensities from all "M" grains satisfying Bragg's law…”
Section: A Mayadas-shatzkes Model For Four-point Resistivity Measurementioning
confidence: 99%
“…The crystalline columns present in μc-Si:H consist of grains of perfect crystal quality separated by grain boundaries. 40 In contrast to the amorphous matrix, the crystalline grains are expected to contain only a small quantity of H. The absence of 1 H-ESEEM in the case of CE centers is therefore a strong indication that these centers are not located in the amorphous phase or at the boundary between crystalline and amorphous phases since the amorphous phase contains H in large concentrations. This conclusion excludes models b and c where CE centers are attributed to interface defects or electrons confined to an inversion layer at the boundary of amorphous and crystalline phases, since in the case of a planar interface the ω I ( 1 H) and 2ω I ( 1 H) peak intensities should indicate a hydrogen density of about half the hydrogen content in the amorphous phase.…”
mentioning
confidence: 99%
“…However, in μc-Si:H, dislocations or point defects are absent in crystalline columns and grains. 40 The only important lattice distortions or crystal defects in crystalline grains are coherent twin boundaries with a high density (twin fault probability λ = 0.1). 40 Theoretical studies of the atomic and electronic structure of silicon twin grain boundaries revealed that they induce shallow localized electronic states.…”
mentioning
confidence: 99%
See 1 more Smart Citation